The implementation of the 1988 DECS minimum library standards for secondary schools in Ilocos Norte an assessment - Acleta, Minda Agustin 1945-
The purpose of the study is to assess the extent of compliance of the secondary school libraries in Ilocos Norte and Laoag City to the 1988 DECS Minimum Library Standards for Secondary Schools. Sixty-five public and private secondary schools in Ilocos Norte and Laoag City were surveyed for this study. Fifty-three of these are located in Ilocos Norte while twelve are in Laoag City. Three public schools in Ilocos Norte were not included in the study because these schools do not offer a complete secondary education at the time of the study. Out of the fifty secondary schools in Ilocos Norte, twenty-eight are public and twenty-two are private. In Laoag City, five are public and seven are private schools.